EFL Students’ Perceptions of Learning Experiences Using the Inquiry Method: A Survey Study - Neni Kustina Sari; Aprilia Yunda Supasa (Universitas Lancang Kuning, 2024)
This study aims to find out how EFL students perceive their learning experience using the inquiry method at Lancang Kuning University. This quantitative study was survey-based in its design. The study employed convenience sampling as a technique of data collection. It was discovered that four elements reflected this survey: critical discourse, authentic investigation, experience-based hypothesis, and conclusion-based transfer. Students' perceptions are merely